2020
DOI: 10.56899/149.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tobacco Stalk Additive Particle Size on the Bond Strength and Formaldehyde Emission of Urea Formaldehyde Bonded Plywood

Abstract: The study investigated the use of native type (Batek) tobacco (Nicotiana tabacum L.) stalk particles from two different mesh sizes – passing 100 mesh but retained at 200 mesh coded as N-100m (74–149 µm) and passing 200 mesh coded as N-200m (< 74 µm) – as additive with both extender and filler property, as well as formaldehyde scavenging property in urea-formaldehyde (UF) resins adhesive formulation used to bond veneers [Falcataria moluccana (Miq.) Barneby & J.W. Grimes] into plywood. The effect of tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The 3% weight loss up to 130 °C was attributed to the release of water from CSB-nZVCu. 23 The breakdown of lignin and carbohydrates takes place in the range of 300−700 °C which is supported by the appearance of a broad endothermic DSC curve in this range 24 as indicated by the 25% weight loss in this region. The slower weight loss after 700 °C that is also accompanied by an exothermic DSC curve beyond this temperature can be due to the oxidation of zerovalent copper to copper oxide (volatile) or breakdown of organic matter, which results in weight loss as well as in the release of heat.…”
Section: Resultsmentioning
confidence: 87%
“…The 3% weight loss up to 130 °C was attributed to the release of water from CSB-nZVCu. 23 The breakdown of lignin and carbohydrates takes place in the range of 300−700 °C which is supported by the appearance of a broad endothermic DSC curve in this range 24 as indicated by the 25% weight loss in this region. The slower weight loss after 700 °C that is also accompanied by an exothermic DSC curve beyond this temperature can be due to the oxidation of zerovalent copper to copper oxide (volatile) or breakdown of organic matter, which results in weight loss as well as in the release of heat.…”
Section: Resultsmentioning
confidence: 87%
“…The use of tobacco flour in the glue-mixes may be beneficial in terms of improved bond strength and reduction of formaldehyde emission (Jimenez and Acda 2018; Jimenez et al 2020). The nicotine and other extractives in the tobacco flour may act as glue-line treatment to provide protection against termites.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works (Jimenez and Acda 2018; Jimenez et al 2020) showed that stalks of native tobacco (Batek) are suitable additive for urea-formaldehyde (UF) glue-mix. However, plywood bonded by those glue-mix formulations has not been tested for TR.…”
Section: Introductionmentioning
confidence: 99%